Persistence and Potential Viable but Non-culturable State of Pathogenic Bacteria during Storage of Digestates from Agricultural Biogas Plants - Maynaud, Geraldine; Pourcher, Anne-Marie; Ziebal, Christine; Cuny, Anais; Druilhe, Céline; Steyer, Jean-Philippe; Wéry, Nathalie (Frontiers in Microbiology, 2016)
Despite the development of on-farm anaerobic digestion as a process for making profitable use of animal by-products, factors leading to the inactivation of pathogenic bacteria during storage of digestates remain poorly described. Here, a microcosm approach was used to evaluate the persistence of three pathogenic bacteria (Salmonella enterica Derby, Campylobacter coli and Listeria monocytogenes) in digestates from farms, stored for later land spreading. Nine samples, including raw digestates, liquid fractions of digestate and composted digestates, were inoculated with each pathogen and maintained for 40 days at 24°C. Concentrations of pathogens were monitored using culture and qPCR methods. The persistence of L. monocytogenes, detected up to 20 days after inoculation, was higher than that of Salmonella Derby, detected for 7-20 days, and of C. coli (not detected after 7 days). In some digestates, the concentration of the pathogens by qPCR assay was several orders of magnitude higher than the concentration of culturable cells, suggesting a potential loss of culturability and induction of Viable but Non-Culturable (VBNC) state. The potential VBNC state which was generally not observed in the same digestate for the three pathogens, occurred more frequently for C. coli and L. monocytogenes than for Salmonella Derby. Composting a digestate reduced the persistence of seeded L. monocytogenes but promoted the maintenance of Salmonella Derby. The effect of NH4+/NH3 on the culturability of C. coli and Salmonella Derby was also shown. The loss of culturability may be the underlying mechanism for the regrowth of pathogens. We have also demonstrated the importance of using molecular tools to monitor pathogens in environmental samples since culture methods may underestimate cell concentration. Our results underline the importance of considering VBNC cells when evaluating the sanitary effect of an anaerobic digestion process and the persistence of pathogens during the storage of digestates and subsequent land spreading.